Стохастическая задача коммивояжера - Серая, Оксана Владимировна; Бачкир, Л. В. (НТУ "ХПИ", 2006)
Розглянуто проблему комівояжера високої розмірності для випадку, коли відстані між пунктами – випадкові величини. Запропоновано декомпозиційний алгоритм рішення задачі. Використано кластеризацію пунктів обходу та генетичний алгоритм пошуку найкоротших локальних шляхів.

The traveling salesman task of high dimension is considered in the case of when distances between points are random variable. The decomposition algorithm of task decision is offered. The cluster of bypass points and genetic algorithm of short local ways search is used.
Keywords: кратчайший маршрут; пункты входа; генетические алгоритмы; расстояния; пункты выхода; пары кластеров